13. The equation of the given function is ![y=4sin[\frac{(t-\frac{4}{3})}{2}]-2](https://tex.z-dn.net/?f=y%3D4sin%5B%5Cfrac%7B%28t-%5Cfrac%7B4%7D%7B3%7D%29%7D%7B2%7D%5D-2)
14. The equation of the cotangent function is ![y=cot[2(t-\frac{1}{3})]+2](https://tex.z-dn.net/?f=y%3Dcot%5B2%28t-%5Cfrac%7B1%7D%7B3%7D%29%5D%2B2)
Step-by-step explanation:
Let us revise the transformation of the trigonometric function:
y = a f[b(x + c)] + d, where
- Amplitude is a
- f represents the trigonometry function
- Period is 2π/b
- Phase shift is c (positive is to the left)
- Vertical shift is d
13.
∵ y = a sin(
), where a is the amplitude
and T is the wave in seconds
∵ The amplitude is 4
∴ a = 4
∵ The period is 4π
∴ T = 4π
From the rules above
∵ The period is 2π/b
∴ T = ![\frac{2\pi }{B}](https://tex.z-dn.net/?f=%5Cfrac%7B2%5Cpi%20%7D%7BB%7D)
∴ 4π = ![\frac{2\pi }{b}](https://tex.z-dn.net/?f=%5Cfrac%7B2%5Cpi%20%7D%7Bb%7D)
- By using cross multiplication
∴ 4π(b) = 2π
- Divide both sides by 4π
∴ b = ![\frac{1}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D)
∵ The phase shift is ![-\frac{4}{3}\pi](https://tex.z-dn.net/?f=-%5Cfrac%7B4%7D%7B3%7D%5Cpi)
∵ c is the phase shift
∴ c = ![-\frac{4}{3}\pi](https://tex.z-dn.net/?f=-%5Cfrac%7B4%7D%7B3%7D%5Cpi)
∵ The vertical shift is -2
∵ d is the vertical shift
∴ d = -2
Now substitutes the values of a, b, c and d in the form of the equation below
∵ y = a sin[b(t + c)] + d
∴ ![y=4sin[\frac{1}{2}(t-\frac{4}{3})]-2](https://tex.z-dn.net/?f=y%3D4sin%5B%5Cfrac%7B1%7D%7B2%7D%28t-%5Cfrac%7B4%7D%7B3%7D%29%5D-2)
You can write it as ![y=4sin[\frac{(t-\frac{4}{3})}{2}]-2](https://tex.z-dn.net/?f=y%3D4sin%5B%5Cfrac%7B%28t-%5Cfrac%7B4%7D%7B3%7D%29%7D%7B2%7D%5D-2)
The equation of the given function is ![y=4sin[\frac{(t-\frac{4}{3})}{2}]-2](https://tex.z-dn.net/?f=y%3D4sin%5B%5Cfrac%7B%28t-%5Cfrac%7B4%7D%7B3%7D%29%7D%7B2%7D%5D-2)
14.
y = cot[b(t + c)] + d
∵ The period = π
∵ The period is 2π/b
- Equate π by 2π/b to find b
∴ π = ![\frac{2\pi }{b}](https://tex.z-dn.net/?f=%5Cfrac%7B2%5Cpi%20%7D%7Bb%7D)
- By using cross multiplication
∴ π(b) = 2π
- Divide both sides by π
∴ b = 2
∵ The phase shift is ![-\frac{1}{3}\pi](https://tex.z-dn.net/?f=-%5Cfrac%7B1%7D%7B3%7D%5Cpi)
∵ c is the phase shift
∴ c = ![-\frac{1}{3}\pi](https://tex.z-dn.net/?f=-%5Cfrac%7B1%7D%7B3%7D%5Cpi)
∵ The vertical shift is 2
∵ d is the vertical shift
∴ d = 2
Now substitutes the values of b, c and d in the form of the equation below
∵ y = cot[b(t + c)] + d
∴ ![y=cot[2(t-\frac{1}{3})]+2](https://tex.z-dn.net/?f=y%3Dcot%5B2%28t-%5Cfrac%7B1%7D%7B3%7D%29%5D%2B2)
The equation of the cotangent function is ![y=cot[2(t-\frac{1}{3})]+2](https://tex.z-dn.net/?f=y%3Dcot%5B2%28t-%5Cfrac%7B1%7D%7B3%7D%29%5D%2B2)
Learn more:
You can learn more about trigonometry function in brainly.com/question/3568205
#LearnwithBrainly